Do minds switch bodies? Dualist interpretations across ages and societies. Issue 4 (2nd October 2018) - Chudek, Maciej; McNamara, Rita Anne; Birch, Susan; Bloom, Paul; Henrich, Joseph
ABSTRACT: Researchers explain cultural phenomena ranging from cognitive biases to widespread religious beliefs by assuming intuitive dualism: humans imagine minds and bodies as distinct and separable. We examine dualist intuition development across two societies that differ in normative focus on thinking about minds. We use a new method that measures people's tendency to interpret ambiguous stimuli using mind-body dualist thinking. We recruited 180 Canadian children (2–10 yrs) along with 42 Indigenous iTaukei Fijian children (5–13 yrs) and 38 Indigenous iTaukei Fijian adults (27–79 yrs) from a remote island community. Participants tracked a named character within ambiguous animations that could be interpreted as a mind-body switch. Animations vary "agency cues" that participants might rely on for dualistic interpretations. Results indicate early emerging dualistic inclinations across populations and reliance on "agency cues" of body proximity and appearance of eyes. "Agency cues" increase dualist interpretations from 10% to 70%, though eyes mattered more for Westernized participants. Overall, statistical models positing that dualist interpretations "emerge early and everywhere" fit our data better than models positing that dualism "develops gradually with exposure to Western cultural traditions." Fijian participants, who normatively avoid focus on minds, offered even more dualistic interpretations when they had less Western cultural exposure (via formal education).